2019
DOI: 10.1080/22797254.2019.1642143
|View full text |Cite
|
Sign up to set email alerts
|

Aerial multispectral imagery for plant disease detection: radiometric calibration necessity assessment

Abstract: This paper focused on the necessity of radiometric calibration to distinguish diseased trees in orchards based on aerial multi-spectral images. For this purpose, two study sites were selected where multispectral images were collected using a multirotor UAV. The impact of radiometric correction on plant disease detection was assessed in two ways: 1) comparison of separability between the healthy and diseased classes using T-test and entropy distances; 2) radiometric calibration effect on the accuracy of classif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Iordache et al [28] applied RF classifier on the classification of Pinus pinaster canopy types (infected, suspicious, and healthy) affected by pine wild and obtained an overall accuracy of 95%. Pourazar et al [27], obtain as overall accuracy 95.58% using five spectral bands and five indices to detect dead and diseased trees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iordache et al [28] applied RF classifier on the classification of Pinus pinaster canopy types (infected, suspicious, and healthy) affected by pine wild and obtained an overall accuracy of 95%. Pourazar et al [27], obtain as overall accuracy 95.58% using five spectral bands and five indices to detect dead and diseased trees.…”
Section: Discussionmentioning
confidence: 99%
“…In order to classify tree canopies into two different classes, healthy and dead trees, supervised machine-learning (ML) classification was used. Among the different object-oriented ML classifiers, the RF algorithm was applied as its performance is one of the most accurate ML algorithms when supervised classification for GEOBIA is conducted [27,28,68,73]. Presented by Breiman [74], RF is an automatic ensemble method based on decision trees where each tree depends on a collection of random variables [75].…”
Section: Object-based Analysis and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, radiometric calibration complicates the process of HLB detection. However, the study showed insignificant effects of radiometric calibration on the discrimination of HLB-infected and healthy trees when the data were collected consistently with similar illumination and atmospheric condition (Pourazar et al 2019). Disease scouting contributes to the control of disease.…”
Section: Detection Of Diseased Fruit Treesmentioning
confidence: 80%
“…Previous studies used QuickBird satellite images to estimate plant traits such as biochemical and biophysical parameters in crops. These include for instance estimating chlorophyll content [ 21 ], the estimation of grain yield [ 22 , 23 ], measuring leaf area index [ 24 , 25 ], the identification of nitrogen status [ 26 ], estimating above-ground biomass [ 10 , 27 ], the detection of crop disease [ 28 , 29 ], estimating crop evapotranspiration [ 30 ] and estimating dry matter [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%